Surgical removal of submacular choroidal neovessels in children: Outcome and literature review. Issue 1 (January 2023) - Abdelmassih, Youssef; EL Khoury, Sylvain; Dureau, Pascal; Edelson, Catherine; Metge, Florence; Caputo, Georges
Purpose: To report on the outcome of surgical submacular choroidal neovascular membrane (CNV) removal in children and to perform a comprehensive review of literature concerning this intervention in children. Methods: In this retrospective, noncomparative, interventional case series, we included 8 eyes of 7 consecutive children with subfoveal choroidal neovascularization treated by pars plana vitrectomy (PPV) and CNV removal. Main outcome measures were visual acuity and complications. Results: Mean age at surgery was 8.6 ± 5.2 years (range: 2–16). Two out of 8 eyes were idiopathic. Corrected-distance visual acuity (CDVA) improved from 1.01 ± 0.45logMAR (range:0.3–1.5) at presentation to 0.60 ± 0.37 (range:0–1) at last follow-up (p = 0.03). Mean follow-up was 3.9 ± 3.9 years. Six eyes received at least one intravitreal injection of bevacizumab prior to surgery. Recurrence occurred in one eye with Best's disease. Literature review revealed a total of 42 cases with the most frequent etiologies being Presumed ocular histoplasmosis syndrome (POHS) and idiopathic CNV. Considering all cases together, mean CDVA improved from 1.00 ± 0.37logMAR to 0.52 ± 0.42 (p < 0.01). CNV recurrence occurred in 11 eyes (22.0%), 7 of which had an inflammatory etiology. Other complications included pigment epithelium tear, atrophy and retinal tear. Conclusion: Surgical removal of CNV is a viable, effective and safe option in children with persistent submacular neovascular membranes.